The yearning for relief : a history of the Sawaba movement in Niger - Walraven, Klaas van, 1958- (Afrika-Studiecentrum series ;, 2013)
In The Yearning for Relief Klaas van Walraven traces the history of the Sawaba movement in Niger and its rebellion against the French-protected regime during the 1960s. The book analyses its guerrilla campaign and failure, followed by the movement's destruction.